2012
DOI: 10.1088/1674-1056/21/8/086105
|View full text |Cite
|
Sign up to set email alerts
|

An AlGaN/GaN HEMT with a reduced surface electric field and an improved breakdown voltage

Abstract: A reduced surface electric field in an AlGaN/GaN high electron mobility transistor (HEMT) is investigated by employing a localized Mg-doped layer under the two-dimensional electron gas (2-DEG) channel as an electric field shaping layer. The electric field strength around the gate edge is effectively relieved and the surface electric field is distributed evenly as compared with those of HEMTs with conventional source-connected field plate and double field plate structures with the same device physical dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…35 For 2DEG, it is possible to compute the exact scattering rates as a function of wave vectors by Fermi's golden rule. 33,39,40 However, this may largely increase the computational load and is not suitable for the hybrid simulation technique. In the simplified treatment, the 3D electronphonon scattering formulation has been generally adopted in the literature 14,19,24,34,35 and is justified by good fittings with experiments.…”
Section: A Electron MC Simulationsmentioning
confidence: 99%
“…35 For 2DEG, it is possible to compute the exact scattering rates as a function of wave vectors by Fermi's golden rule. 33,39,40 However, this may largely increase the computational load and is not suitable for the hybrid simulation technique. In the simplified treatment, the 3D electronphonon scattering formulation has been generally adopted in the literature 14,19,24,34,35 and is justified by good fittings with experiments.…”
Section: A Electron MC Simulationsmentioning
confidence: 99%
“…Thus, drain breakdown voltage is enhanced and drain current collapse is lessened. [11][12][13][14][15][16][17][18] Gate field plates have also been implemented to demonstrate a drain breakdown voltage of 570 V by extending the gate on top of silicon nitride (SiN x ) toward the drain contact. 19 Hikita et al opened a via through the epitaxial layer to the front side of the device to connect the frontside source to a backside grounding electrode and achieved both low on-state resistance (1.9 mX cm 2 ) and high breakdown voltage of 350 V. 20 Lu et al 18 also demonstrated the effect of source field plate, which improved the breakdown voltage from 55 to 155 V.…”
Section: Improvement Of Drain Breakdown Voltage With a Back-side Gatementioning
confidence: 99%
“…Gallium Nitride (GaN) has now been widely used for high electron mobility transistors (HEMT) due to its high mobility and also because of its wide bandgap which endows it the property of high breakdown voltage and allows it to be used for high voltage applications [8][9]. GaN nanowires have been in fabrication processes for a long time [10][11] and been used for photo-detection and photoluminescence applications [12][13].…”
Section: Introductionmentioning
confidence: 99%